2012
DOI: 10.2110/jsr.2012.50
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Siderite Concretions In Microenvironments of Methanogenesis Developed In A Sulfate Reduction Zone: An Exception Or A Rule?

Abstract: The Mississippian shales from Wardie (Scotland) were deposited in a large normally brackish-water basin. They host siderite concretions with d 13 C values ranging from 23.5 to 12.1% which show that sulfate reduction and methanogenesis contributed to the production of bicarbonate. Fossils are found within each of the concretions, suggesting that the decay of these organic remains provided a catalyst for concretionary growth. The pore water was freshened, which is indicated by the very negative d 18 O values (fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
35
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 51 publications
6
35
1
Order By: Relevance
“…caused by ammonia production); subsequently these may function as nucleation centers for binding additional bicarbonate scavenged from pore-water (Allison, 1988). Geochemical studies of carbonate concretions in marine environments confirm the role of organic matter decay processes (AOM, SBR, methanogenesis) in their early diagenetic formation (Claypool and Kaplan, 1974;Irwin et al, 1977;Coleman, 1993, Bojanowski andClarkson, 2012). Recently, it has been suggested that nodules on large carcasses of vertebrates could be linked to the activity of sulphate reducing bacteria (Shapiro and Spangler, 2009), and a correlation with the evolution of modern whale-falls communities has been hypothesized (e.g., Danise et al, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…caused by ammonia production); subsequently these may function as nucleation centers for binding additional bicarbonate scavenged from pore-water (Allison, 1988). Geochemical studies of carbonate concretions in marine environments confirm the role of organic matter decay processes (AOM, SBR, methanogenesis) in their early diagenetic formation (Claypool and Kaplan, 1974;Irwin et al, 1977;Coleman, 1993, Bojanowski andClarkson, 2012). Recently, it has been suggested that nodules on large carcasses of vertebrates could be linked to the activity of sulphate reducing bacteria (Shapiro and Spangler, 2009), and a correlation with the evolution of modern whale-falls communities has been hypothesized (e.g., Danise et al, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…The range of depositional set tings doc u mented in the Oravica River sec tion, to gether with the abun dance of wood frag ments, points clearly to the non-ma rine or i gin of the ba sin fill in this area. This is fur ther sup ported by the sphe roi dal tex tures of sid er ite con cre tions, be cause such tex tures ap pear nei ther in fully ma rine, nor in brack ish-wa ter en vi ron ments (Bojanowski and Clark son, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, some kind of a concentric mechanism was also involved in the concretionary growth (cf. Bojanowski & Clarkson, ). The proposed interpretation proves that the decreasing content of cement towards the edge of the concretions, which generally is typical, is not necessarily related to conventionally presumed concentric outward growth, but can be the result of a combination of pervasive and inward concentric growth mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the elemental and stable C and O isotope compositions of siderite concretions commonly provide information about the sources of pore‐water and the DIC therein, and may help to characterize the depositional environment (Mozley, ; Mozley & Wersin, ). Fresh‐water siderite concretions are reported to have precipitated from meteoric or brackish water, mostly due to Fe reduction or microbial methanogenesis (Curtis & Coleman, ; Curtis et al ., ; Mozley & Carothers, ; Mozley & Wersin, ; Middleton & Nelson, ; Bojanowski & Clarkson, ). Sulphate reduction, although common in marine sediments, does not usually operate in fresh‐water settings due to very low sulphate concentrations (Berner, ).…”
Section: Introductionmentioning
confidence: 99%